Milk bottle : an animated short. - Cheng, Yu Chao. (2009)
With an increase in pace of life in the society, there is an increase in concern that one fails to appreciate life and the people around them. In search of fame and glory, a person competes unrelentingly with others. The story strives to deliver the message on the desire and competitive nature of human which has blinded the everyday life and the irony when unexpected situation happens. The development of characters had been arranged in a metamorphic time manner accordingly. The arrangement of the different settings of the characters in their phase of life brings about a deeper meaning and intensity of the competitive struggles in life with the use of a simple plot. By means of software applications like Adobe Flash, an animated story was developed to be shared and enjoyed with the audience.